DYNAMICS OF CHARACTER EDUCATION THROUGH THE OUTBOUND TRAINING ACTIVITIES FOR STUDENTS ON THE CAMPUS - Ryan Firdiansyah Suryawan; Dewi Dyah Widyastuti (Dinasti International Journal of Education Management And Social Science, 2020)
This research uses qualitative descriptive method by taking the results of the implementation of the data that has been unsettled outbound management training activities where researchers are also lecturers as Chairman of the Committee in the activities of outbound management training in aviation aviation high school jakarta, both using the method of the study of literature to support the data in the discussion. The results of this research: response to these conditions, AVIATION flight College help participate in back, straighten and encourage positive behavior through character education so that graduates into a human who has a soft skill and skill that is difficult. Character education for flight school students carried out off-campus in the open in the form of training that includes a variety of outbound activities management training by type of training provided is the emergency aircraft, the formation of water, the life craft, landing nets and hoist outbound Please. The purpose of education is to form character and cultivate good behaviour or attitude and value so that they can interact, communicate, and live together in accordance with the norms of the community. Tangible results seen from students who have undergone study. Through outbound training, it is expected that students can mentally ready, tenacious, confident, caring, helpful and accountable to God Almighty, self, community and nation that are implemented in real life everyday.